Inhibition of Acid Sphingomyelinase by Antidepressants Counteracts Stress-Induced Activation of P38-Kinase in Major Depression - Grassmé, Heike; Jernigan, Peter L.; Hoehn, Richard S.; Wilker, Barbara; Soddemann, Matthias; Edwards, Michael J.; Müller, Christian P.; Kornhuber, Johannes; Gulbins, Erich (Neurosignals, 2015)
Major depressive disorder is a common disease with serious morbidity, including increased risk of death from suicide. Major depressive disorder is treated with antidepressants. However, the molecular targets of antidepressants remained ill-defined and require further elucidation.Mice were treated with corticosterone to induce stress, amitriptyline and the p38-kinase (p38K) inhibitor SB239063 or a combination of these drugs. Phosphorylation of p38K in hippocampal neurons was determined by immunostaining with a phospho-specific antibody, neuronal proliferation using BrdU-labelling and behaviour employing a set of behavioural tests.Corticosterone induced phosphorylation/activation of p38K in the hippocampus in vivo. Antidepressants reversed the effect of corticosterone on p38K activation in wildtype mice, but had no effect in acid sphingomyelinase-deficient animals. Corticosterone also reduced neurogenesis and triggered depression-like behavioural changes, effects that were prevented by pharmacological inhibition of p38K.Stress induces p38K phosphorylation/activation in the hippocampus and thereby reduces neurogenesis and induces depression-like symptoms, events that are prevented by antidepressants via inhibition of the acid sphingomyelinase/ceramide system.
EVALuna2:23741